Eradication Efficacy of Modified Dual Therapy Compared with Bismuth-Containing Quadruple Therapy as a First-Line Treatment of Helicobacter pylori - Yang, Jing; Zhang, Yi; Fan, Ling; Zhu, Yang-Jie; Wang, Ting-Yi; Wang, Xing-Wei; Chen, Dong-Feng; Lan, Chun-Hui (The American journal of gastroenterology, 2019)
This study assessed the effectiveness, adverse events, patient adherence, and costs of modified dual therapy compared with bismuth-containing quadruple therapy for treating Helicobacter pylori infection in Chinese patients. We also sought to determine whether modified dual therapy could be used as an alternative first-line treatment for H. pylori infection. A total of 232 H. pylori-infected, treatment-naive patients were enrolled in this open-label, randomized controlled clinical trial. Patients were randomly allocated into 2 groups: the 14-day modified dual therapy group and the bismuth-containing quadruple therapy group. Eradication rates, drug-related adverse events, patient compliance, and drug costs were compared between the 2 groups. The modified dual therapy group achieved eradication rates of 87.9%, 91.1%, and 91.1% as determined by the intention-to-treat, per-protocol, and modified intention-to-treat analyses, respectively. The eradication rates were similar compared with the bismuth-containing quadruple therapy group: 89.7%, 91.2%, and 90.4%. In addition, modified dual therapy ameliorated variations in the CYP2C19, IL-1B-511, and H. pylori VacA genotypes. There were no significant differences in the compliance rates between the 2 groups. The modified dual therapy group exhibited significantly less overall side effects compared with the bismuth-containing quadruple therapy group (P < 0.001). Furthermore, the cost of medications in the modified dual therapy was lower compared with that in the bismuth-containing quadruple therapy. Modified dual therapy at high dose and administration frequency is equally effective and safer and less costly compared with bismuth-containing quadruple therapy.